Cu4MnGe2S7 and Cu2MnGeS4: two polar thiogermanates exhibiting second harmonic generation in the infrared and structures derived from hexagonal diamond. Issue 47 (19th November 2021) - Glenn, Jennifer R.; Cho, Jeong Bin; Wang, Yiqun; Craig, Andrew J.; Zhang, Jian-Han; Cribbs, Marvene; Stoyko, Stanislav S.; Rosello, Kate E.; Barton, Christopher; Bonnoni, Allyson; Grima-Gallardo, Pedro; MacNeil, Joseph H.; et al.
Abstract : The synthesis, structure, and physicochemical characterization of two diamond-like semiconductors are reported. Both compounds display second harmonic generation, bandgaps around 2 eV and wide windows of optical transparency in the infrared. Abstract : The new, quaternary diamond-like semiconductor (DLS) Cu4 MnGe2 S7 was prepared at high-temperature from a stoichiometric reaction of the elements under vacuum. Single crystal X-ray diffraction data were used to solve and refine the structure in the polar space group Cc. Cu4 MnGe2 S7 features [Ge2 S7 ] 6− units and adopts the Cu5 Si2 S7 structure type that can be considered a derivative of the hexagonal diamond structure. The DLS Cu2 MnGeS4 with the wurtz-stannite structure was similarly prepared at a lower temperature. The achievement of relatively phase-pure samples, confirmed by X-ray powder diffraction data, was nontrival as differential thermal analysis shows an incongruent melting behaviour for both compounds at relatively high temperature. The dark red Cu2 MnGeS4 and Cu4 MnGe2 S7 compounds exhibit direct optical bandgaps of 2.21 and 1.98 eV, respectively. The infrared (IR) spectra indicate potentially wide windows of optical transparency up to 25 μm for both materials. Using the Kurtz–Perry powder method, the second-order nonlinear optical susceptibility, χ (2), values for Cu2 MnGeS4 and Cu4 MnGe2 S7 were estimated to be 16.9 ± 2.0 pm V −1 and 2.33 ± 0.86 pm V −1, respectively, by comparing with an optical-quality standard reference material, AgGaSe2 (AGSe). Cu2 MnGeS4 was found to be phase matchable at λ = 3100 nm, whereas Cu4 MnGe2 S7 was determined to be non-phase matchable at λ = 1600 nm. The weak SHG response of Cu4 MnGe2 S7 precluded phase-matching studies at longer wavelengths. The laser-induced damage threshold (LIDT) for Cu2 MnGeS4 was estimated to be ∼0.1 GW cm −2 at λ = 1064 nm (pulse width: τ = 30 ps), while the LIDT for Cu4 MnGe2 S7 could not be ascertained due to its weak response. The significant variance in NLO properties can be reasoned using the results from electronic structure calculations.